Legal Protection of Doctors As Executors of Conditional Abortions For Rape Victims - Indrawati; Soetarno; Ninis Nugraheni (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
This study explores the historical and contemporary practices of abortion, focusing on the legal and psychological implications for rape victims and the role of doctors as executors. Abortion has been practiced since ancient times using various methods across different cultures. Modern discussions about abortion remain contentious, especially concerning the rights of rape victims who often face severe psychological trauma. The primary objective of this research is to examine the evolution of abortion laws in Indonesia, particularly those providing legal protection for medical professionals. This normative juridical research employs statute and conceptual approaches to analyze laws, regulations, and legal doctrines, connecting them with current positive law to address the main thesis issues. Key findings indicate that Indonesian laws have progressively recognized the necessity of abortion in specific circumstances, culminating in the 2023 amendments to the Criminal Code and Health Law. These legal frameworks aim to protect women's mental health and uphold their human rights, as enshrined in international conventions. The research concludes that although legal provisions for abortion have progressed, there is still a need for improved implementation and support systems to safeguard medical professionals due to lingering ambiguities in the law.